2021
DOI: 10.1002/adhm.202170095
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Electrospun 3D Gelatin Nanofiber Sponge for Rapid Hemostasis (Adv. Healthcare Mater. 20/2021)

Abstract: Nanofiber Sponges In article number 2100918, Jinglei Wu, Xiumei Mo, and co‐workers develop a novel conjugate electrospinning strategy to prepare a 3D nanofiber sponge with low density, high surface area, compressibility. This method can be widely used in the preparation of various polymer nanofiber sponges. The obtained gelatin nanofiber sponge holds great potential as an absorbable hemostatic agent for rapid hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Fibers are one of the most frequently used hemostatic carriers. [ 10,29–31 ] Thus, we fabricated polycaprolactone (PCL) nanofibers to support keratin films and evaluated their hemostatic activities ( Figure A). Figure 2B shows the morphology of as‐prepared thin films under scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…Fibers are one of the most frequently used hemostatic carriers. [ 10,29–31 ] Thus, we fabricated polycaprolactone (PCL) nanofibers to support keratin films and evaluated their hemostatic activities ( Figure A). Figure 2B shows the morphology of as‐prepared thin films under scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…The gelatin nanofiber sponge activates platelets in large quantities to promote the formation of the platelet embolism and simultaneously escalated the extrinsic and intrinsic coagulation pathways. In vivo studies using a rabbit ear artery injury model and a rabbit liver demonstrated the superior capability of the gelatin nanofiber sponge in forming stable blood clots in the shortest time with the least blood loss [39] . Overall, the amphiphilicity of the nanofiber dressings and the incorporated clotting factors play significant roles in hemorrhage control.…”
Section: Control Hemorrhagementioning
confidence: 98%
“…Similarly, Mo et al . reported ultralight gelatin nanofiber sponges for hemostasis [39] . The gelatin nanofiber sponge activates platelets in large quantities to promote the formation of the platelet embolism and simultaneously escalated the extrinsic and intrinsic coagulation pathways.…”
Section: Control Hemorrhagementioning
confidence: 99%
“…[ 17,38,39 ] However, MN patches have not been applied to wounds, where underlying blood capillaries are damaged and exposed. Although recent reports have successfully demonstrated wound closure as a regenerative dressing material, [ 40–43 ] previous studies focused on incision wounds, which are less frequently caused by accidents. [ 40,44–47 ]…”
Section: Introductionmentioning
confidence: 99%